Efectos de las auxinas y citoquinininas sobre el desarrollo productivo en el cultivo de maracuya (Passiflora Edulis) en el Ecuador - Izquierdo Guapulema, Ronny Steven (2022)
In this thesis, research was carried out on the Effects of Auxins and Cytokinins on Productive Development in the Cultivation of Maracuya In Ecuador, according to the National Institute of Agricultural Research (INIAP, 2014), in Ecuador, the maracuya (Passiflora edulis) has about 247,973 tons of production and a average productivity of 8.6 tons per hectare. Both forms of maracuyá are cultivated in Ecuador, but the one that is cultivated with the greatest extent is the yellow one. The effects of phytohormones result in the best yield and longer production time of the crop, reducing losses for the grower and emphasising the benefits of applying auxins and cytokines in the correct way. The primary difficulty for field farmers is that they are associated with the occupation of conventional crops, which is the primary cause of stress and reduced productivity. The research aims to provide information that will be useful to the entire farming community engaged in the production of maracuya to improve low production and ways to prevent it. Phytohormones such as auxins and cytokinins in the cultivation of passion fruit offer the opportunity to improve the production system. These substances have unique characteristics of absorption into plant tissue and mobilized to a reaction site before producing the desired effect. The main objective of this work was to describe the positive effects of auxins and cytokinins in the cultivation of maracuya.